Antonia's Mannish Behavioral Transition in Willa Cather's Novel My Antonia (Journal of the College of Education for Women, 2019)
This paper aims to study Antonia's character and her mannish behavioral transition throughout the novel entitled My Antonia. Willa presents Antonia who shows her resolution and courage in facing and dealing with personal dilemmas and social circumstances. Willa portrays Antonia, who struggles in the new society and culture by working hard in changing the salty land of Nebreska and her destiny . Working in salty land day and night forces Antonia to lose her tender behavior and her beauty as a woman is changed too. She achieves her goals to live with her family in a new place with a dignity and respect though she looks like a man in her strength and body built . Willa Cather tries to explain that the major figure in her novel,Antonia, is characterized by strength, fortitude, and resolution. She is able to face difficulties of life and never surrender to them.